Taxonomic assessment of seaweed community from the coastal areas of Bintulu, Sarawak, Malaysia - Zawawi, Mohd Hafizbillah; Idris, Mohd Hanafi; Mustafa Kamal, Abu Hena; Wong, Sing King (Research and Development Office, Prince of Songkla University, 2015)
Basic taxonomic information forms the important basis for the documentation, resource management and utilization of marine biodiversity such as seaweeds. A taxonomic assessment of seaweeds in the coastal areas of Bintulu, Sarawak, East Malaysia, was conducted monthly from May 2011 to May 2012. Species composition was recorded following NaGISA protocols, direct observation, and SCUBA and snorkeling techniques. A total of 54 species were identified, classified into Rhodophyta (23 species), Chlorophyta (16 species) and Phaeophyta (15 species). The highest abundance was recorded at Kuala Similajau (25 species) while the lowest was recorded at Kuala Nyalau (12 species). As the present study was conducted by examining species collected from both rocky shores and the reef area for the first time, a higher number of species was documented compared to previous studies conducted in the same general area but focusing only on particular habitats.Thirty species found in the current survey represent new records for the locality including some with economic potentials.